Bitcoin Dalam Perspektif Hukum Islam : Analisis Legalitas Dan Transaksi Syariah - Fatimah Azzahara (Quranomic: Jurnal Ekonomi dan Bisnis Islam, 2026)
Bitcoin is a form of cryptocurrency that has been growing rapidly in recent years. Its existence raises various debates, including in the context of Islamic law. This paper discusses the definition and characteristics of Bitcoin, and reviews its legal status from a sharia perspective. The discussion includes scholars' views on the halalness or haramnessing of Bitcoin, an analysis of the contracts involved in Bitcoin transactions, and the risks and challenges of its use according to the principles of muamalah. Based on a study of classical and contemporary fiqh sources, as well as fatwas of Islamic institutions, it is concluded that the legal status of Bitcoin is still ijtihadi and open to further study. The assessment of the validity of Bitcoin in Islamic law is highly dependent on the context of its use, the value of benefits (maslahah), and the potential for harm